Management of SIM-RS in the Prevention of Incomplete Daily Census Inpatients at Ciremai Hospital Level III 03.06.01 Cirebon - Tryasmoro, Fikry; Purbasari, Dwiyanti; Rahayu, Rosalia (Jurnal Kesehatan Mahardika, 2022)
The results of a preliminary study conducted at hospital Tingkat III 03.06.01 Ciremai Cirebon, that the daily inpatient census form in August 2020 to December 2020 there are complete inpatient daily census forms, namely 92% (1340) and 8% (115) which are incomplete. This type research uses quantitative descriptive. The population of this study were inpatient nurses and midwives, head of inpatient care, head of inpatient installation, and medical recorders.. The sample technique uses proportional random sampling. The research instrument used a questionnaire. The analysis of this study uses univariate analysis. The research results obtained that the SIM-RS governance in prevention of incomplete census daily inpatient of appropriate, namely as many as 27 (75,0%). The organizational structure of the SIM- RS installation in carrying out the daily inpatient census is appropriate. The human resources of the SIM-RS installation in carrying out the daily inpatient census are appropriate. The framework in the SIM-RS installation in the implementation of the daily inpatient census, namely 15 (41.7%) were appropriate. The hospital medical records are strived to improve coordination, monitoring and evaluation of the management of hospital management information system relating to the management of the daily inpatient census with the head of the inpatient installation periodically.